2019
DOI: 10.1177/0748730419844650
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Induces an Earlier Chronotype in Both Mice and Women

Abstract: Daily rhythms generated by endogenous circadian mechanisms and synchronized to the light-dark cycle have been implicated in the timing of birth in a wide variety of species. Although chronodisruption (e.g., shift work or clock gene mutations) is associated with poor reproductive outcomes, little is known about circadian timing during pregnancy. This study tested whether daily rhythms change during full-term pregnancies in mice and women. We compared running wheel activity continuously in both nonpregnant ( n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 73 publications
2
27
0
Order By: Relevance
“…The use of shift workers and electric lighting has disrupted this cycle and disturbed the optimal levels of melatonin in the blood as well [118,119]. The levels of melatonin in the follicular fluid during ovulation are higher than the levels found in human blood [120,121]. Several studies have reported the role of melatonin is seen not only in the labor and delivery mechanisms but also in ovulation and early pregnancy.…”
Section: Melatoninmentioning
confidence: 99%
“…The use of shift workers and electric lighting has disrupted this cycle and disturbed the optimal levels of melatonin in the blood as well [118,119]. The levels of melatonin in the follicular fluid during ovulation are higher than the levels found in human blood [120,121]. Several studies have reported the role of melatonin is seen not only in the labor and delivery mechanisms but also in ovulation and early pregnancy.…”
Section: Melatoninmentioning
confidence: 99%
“…Physiologic-metabolic adaptations occur as females transition through reproductive states, with maternal circadian rhythms of behavior and physiology changing throughout pregnancy and lactation [23][24][25][26][27][28][29][30]. Previous studies reported overall activity levels of pregnant women were decreased and onset of activity shifted to an earlier time relative to non-pregnant states [31]. We found no difference in time of waking or start of sleep time between gestational weeks 22 and 32 in this population of women [18], but there was a shift in time of peak of activity to nearly an hour earlier in the third trimester relative to second trimester.…”
Section: Circadian Rhythms Become Attenuated As Pregnancy Progresses mentioning
confidence: 99%
“…Maternal adaption in pregnancy induces changes in circadian rhythms [10] with marked alterations in the expression of circadian clock genes [11,12]. More specifically, changes in maternal peripheral clock gene expressions across pregnancy drive downstream shifts in circadian expression of certain metabolic genes, such as glucoregulatory genes Pck1, G6Pase and Gk to support healthy pregnancy [12].…”
Section: Introductionmentioning
confidence: 99%